(Nie)skuteczność instytucjonalnego wsparcia udzielanego osobom wykolejającym się w trajektorii ich przestępczej kariery - Noszczyk-Bernasiewicz , Monika (Studia Edukacyjne, 2018)
The article contains an in-depth qualitative analysis of 60 biographies of juvenile offenders in terms of the institutional (in)effectiveness of counteracting crime in the period before being placed in a closed facility. The analysis of the data shows that placement in a correctional facility is preceded by the application of many educational measures from supervision order to the decision to place a minor in an educational facility. Based on the collected data, it is possible to find a bad way of exercising parental care over the delinquents, and especially the ineffectiveness of the reactions undertaken by state institutions - remedial actions – including the family court.